2002
DOI: 10.1016/s0014-5793(02)02437-7
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of mitochondrial and plastid activity of Plasmodium falciparum by minocycline

Abstract: We previously reported the superior effect of minocycline against drug-resistant Plasmodium falciparum in vitro. Here, we report that RT-PCR for falciparum parasites treated with minocycline revealed reduced levels of RNA transcripts of the mitochondrion-encoded genes such as the COI and Cyb genes, as well as the plastid-encoded RNA polymerase subunit (rpoB/C) gene. However, we detected no apparent effects of the antibiotic on the transcription of merozoite surface antigen and small subunit rRNA genes encoded … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
26
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(27 citation statements)
references
References 25 publications
1
26
0
Order By: Relevance
“…DOX would inhibit the synthesis of nucleotides and deoxynucleotides in P. falciparum (53) at concentrations much higher than those observed in vivo (200 M). The in vitro exposure of P. falciparum to minocycline would also (21). One study showed that DOX acts specifically on the apicoplast of P. falciparum (11) and, to a lesser extent, on the mitochondrion, the division of which is inhibited at the end of the parasite cycle.…”
Section: Downloaded Frommentioning
confidence: 99%
“…DOX would inhibit the synthesis of nucleotides and deoxynucleotides in P. falciparum (53) at concentrations much higher than those observed in vivo (200 M). The in vitro exposure of P. falciparum to minocycline would also (21). One study showed that DOX acts specifically on the apicoplast of P. falciparum (11) and, to a lesser extent, on the mitochondrion, the division of which is inhibited at the end of the parasite cycle.…”
Section: Downloaded Frommentioning
confidence: 99%
“…Thiostrepton is a potent inhibitor of P. falciparum growth in vitro (46,60) and in vivo (64). Rifampin blocks bacterial-type transcription and abrogates mRNA production by the apicoplast-carried rpoB gene (encoding the DNA-directed RNA polymerase beta subunit) (42,43,46). The targets of ciprofloxacin, thiostrepton, and rifampin are reported in the Babesia bovis genome sequence database (20).…”
mentioning
confidence: 99%
“…Tetracyclines and macrolides have antimicrobial activity, alone and in combination with other drugs, against other eukaryotic organisms, including algae (10), fungi (11,14,22), and protozoa (6,12). Although the mechanism of action of these drugs on eukaryotic organisms is not completely understood, the main mechanisms described include the inhibition of protein synthesis (14,17) and selective inhibition of both mitochondrial and plastid activity (12) and intracellular calcium release (22).…”
mentioning
confidence: 99%
“…Although the mechanism of action of these drugs on eukaryotic organisms is not completely understood, the main mechanisms described include the inhibition of protein synthesis (14,17) and selective inhibition of both mitochondrial and plastid activity (12) and intracellular calcium release (22). However, there have been no susceptibility studies using these classes of antibiotics against P. insidiosum.…”
mentioning
confidence: 99%